A new species of the Aenictus pachycerus species group (Hymenoptera: Formicidae) from the Western Ghats, India, with a key to members of the A. pachycerus species group - Mohammad Abdus Shakur; Sumanta Bagchi (Soil Organisms)
A new species of the genus Aenictus Shuckard, 1840 is described from the Western Ghats region, India, under the name A. kodagura Shakur & Bagchi, sp. nov. based on the worker caste. The new species belongs to the Aenictus pachycerus species group and shares affinities with A. sirenicus Yamane & Wang, 2015, in having a smooth head, smooth pronotum and sculptured propodeum, pedunculate petiole and postpetiole. The new species can be differentiated from A. sirenicus by the presence of subpetiolar process, propodeum being slightly convex in profile, petiole and postpetiole being comparable in length, and a uniform pale brown coloration of the body. The holotype was collected from coffee plantations in Kodagu district of Karnataka.